Circular Economy Approach to Enhance Soil Fertility Based on Recovering Phosphorus from Wastewater - Tolulope Ayeyemi; Ramiro Recena; Ana María García-López; Antonio Delgado (Agronomy, 2023)
Phosphorus (P) is a non-renewable resource whose future scarcity will constrain agricultural sustainability. Thus, to ensure this sustainability, a circular economy approach involving the use of recycled P sources is needed. The objective of this study was to assess the fertilizer effect of two recycled P products that can be obtained from water purification: vivianites and struvites. Five vivianites (one synthetic, one obtained from industrial process, and three from water purification) and two struvites (named A and B) from diverse origins were compared with soluble mineral P fertilizer (superphosphate) in a pot experiment using wheat at two P rates (50 and 100 mg P kg−1) in two Mediterranean soils. Struvites performed similarly to superphosphate and outperformed all types of vivianites in terms of dry matter (DM) yield and P uptake. Industrial and synthetic vivianites, led to higher DM yield and P uptake by plants than vivianites from water purification. Synthetic and industrial process vivianites increased Olsen P in soils after harvesting, relative to non-fertilized soils. Differences between vivianites can be explained by the different Fe2+ to Fe3+ ratios, the different crystal sizes, and morphology. Struvite B can replace 65–92% superphosphate on a P uptake basis, and 94–154% on a DM yield basis (the range depends on the P rate). Vivianite from industrial process can replace 54–75% of superphosphate on a DM basis, depending on the P rate. Thus, struvites were as efficient as superphosphate as P fertilizer. However, the results obtained with industrial process vivianite are promising with a view to its potential use in agriculture.